Urinary fluoride output in children following the use of a dual-fluoride varnish formulation - Kaneshiro Olympio, Kelly Polido; da Silva Cardoso, Vanessa Eid; Borro Bijella, Maria Fernanda; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Rabelo Buzalaf, Marilia Afonso (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2009)
Objective: This study evaluated the bioavailability of fluoride after topical application of a dual-fluoride varnish commercially available in Brazil, when compared to Duraphat T. Material and methods: The urinary fluoride output was evaluated in seven 5-year-old children after application of the fluoride varnishes, in two different phases. In the first phase (I), children received topical application of the fluoride varnish Duofluorid XII (2.92% fluorine, calcium fluoride + 2.71% fluorine, sodium fluoride, FGM (TM)). After 1-month interval (phase II), the same amount (0.2 mL) of the fluoride varnish Duraphat (2.26% fluorine, sodium fluoride, Colgate T) was applied. Before each application all the volunteers brushed their teeth with placebo dentifrice for 7 days. Urinary collections were carried out 24 h prior up to 48 h after the applications. Fluoride intake from the diet was also estimated. Fluoride concentration in diet samples and urine was analyzed with the fluoride ion-specific electrode and a miniature calomel reference electrode coupled to a potentiometer. Data were tested by ANOVA and Tukey's post hoc test (p < 0.05). Results: There were significant differences in the urinary fluoride output between phases I and II. The use of Duofluorid XII did not significantly increase the urinary fluoride output, when compared to baseline levels. The application of Duraphat caused a transitory increase in the urinary fluoride output, returning to baseline levels 48 h after its use. Conclusions: The tested varnish formulation, which has been shown to be effective in in vitro studies, also can be considered safe.
Keywords: Fluorine; Varnishes; Urine; Toxicity; Children